Effect of humidity upon turgor, germ tube growth, appressorium formation in vitro and infectivity of conidia from Blumeria graminis f. sp. tritici - and S. FRIEDRICH, C. BOYLE, H. BOYLE (Indian Phytopathology, 2002)
The influence of RH on conidiogenesis and germination of B. [Erysiphe] graminis f.sp. tritici, the cause of powdery mildew of wheat, was investigated in growth chambers. Conidiogenesis at high RH resulted in a higher conidial water content compared with conidia formed under drier conditions. In general, a RH of 97% was opt. for maintenance of conidial turgor. Above that level, the number of burst conidia increased. With conidia formed under drier conditions, opt. germ tube growth and appressorium development were obtained at 97% RH. Conidia exposed to higher humidities during conidiogenesis had a somewhat higher opt. No appressoria were formed at humidities _92%. Exposure of conidia to dry conditions (22.5% RH, 20degC) on glass slides resulted in the number of turgid conidia decreasing to zero within 24 h, with a sharp drop between 5 and 8 h of exposure. The longer the conidia were exposed to such dry conditions, the fewer colonies subsequently developed on inoculated test plants. The humidity level during conidiogenesis had no detectable influence on fungal development and infection after exposure of the conidia to dry conditions. The differing water retention capacity of conidia formed under different humidity regimes and the effect of dry conditions on turgor reduction and infectivity are discussed.